Sperm morphology of two marine neogastropods from the southwestern Atlantic Ocean (Caenogastropoda: Volutidae and Olividae) - Giménez, Juliana (2009)
The testes of Caenogastropoda typically produce two types of spermatozoa, euspermatozoa and paraspermatozoa. The structures of both morphological forms of sperm contribute to our understanding of reproductive biology, and also have been useful to elucidate taxonomic and phylogenetic relationships among gastropods. The following account describes the ultrastructure and the possible systematic importance of euspermatozoa in two species, Adelomelon beckii from the family Volutidae and Olivancillaria deshayesiana from the family Olividae. The euspermatozoa of these species are characterized by: the presence of an acrosomal vesicle with an apical bleb and accessory membrane; a nucleus that is long and tubular with the axoneme penetrating the nucleus; a midpiece with mitochondrial elements coiled helically around the axoneme; a glycogen piece; and a short end piece.  A constriction in the acrosomal vesicle and mitochondrial elements that appear U-shaped and electron dense in cross section are features that are present in the studied taxa, but have not been reported outside of the Neogastropoda.